Energetic scales in a bluff body shear layer. (25th September 2019) - Moore, D. M.; Letchford, C. W.; Amitay, M.
Abstract : A detailed experimental campaign into separated shear layers stemming from rectangular sections (having aspect ratios of 5 : 1, 3 : 1 and 1 : 1) was carried out at Reynolds numbers range between 1.34× 10^4 and 1.18× 10^5 based on the body thickness. Particle image velocimetry was used to locate the highest concentration of fluctuations in the velocity field and subsequent hot-wire measurements at those locations provided adequate spectral resolution to follow the evolution of various instabilities that are active within the separated shear layer. Similar to recent findings by this same group, the shear layer behaviour is observed to contain a combination of Reynolds invariant characteristics, including its time-averaged position, while other properties demonstrate clear Reynolds number dependency, including the spatial amplification of turbulent kinetic energy. Additional results here show that the ratio of side lengths of the body is a key parameter in revealing these effects. One reason for this is the level of coupling between modes of instability, which is evaluated using two-point correlation methods. These findings indicate that the separated shear layer on a bluff body is highly nonlinear. A specific set of scales responsible for these unique behaviours is identified and discussed, along with their relationship to other scales in the flow.